Synthesis and characterization of photocatalyst from titanium dioxide and zinc oxide supported on laponite clay RD - Lemos, Péricles Joaquim Hilário da Cunha; Batista, Tatiana; Machado, Douglas Silva (Seven Editora, 2023)
The industrial and agricultural expansion together with the growth of cities has raised environmental questions about the disposal of effluents and their possible treatments. Organic wastes with industrial phenolic compounds and pesticides are not treated properly in WTPs, where the methods used as flocculation and decantation are inefficient for this class of compounds. In the last decades, ways of eliminating such compounds from effluents have been studied, one of these techniques being the Advanced Oxidative Processes (POA). In POA, through a generated radical, it is possible to mineralize harmful compounds to innocuous compounds such as CO2 and H2O. The present work aimed to synthesize and characterization of two photocatalysts based on titanium dioxide and zinc oxide capable of degrading organic molecules using POA, through natural solar irradiation. The synthesis was performed using titanium dioxide (TiO2) and zinc oxide (ZnO), which in their crystalline forms have photocatalytic properties. TiO2 and ZnO were supported on a synthetic clay (Laponite RD), which has a large adsorptive capacity. The characterization of the composites was performed utilizing infrared spectroscopy (FTIR) and X-ray fluorescence (XRF), where morphological and composition characteristics of the synthesized composites were obtained. To understand the photocatalytic behavior of the materials, a study of the speed of degradation of the methylene blue organic dye (AM) in the presence of sunlight was performed. The photodegradation kinetics was accompanied by the UV-visible spectroscopy technique, where the efficiency of the new photocatalysts increases about 4 times the degradation speeds. DOI:https://doi.org/10.56238/devopinterscie-191